2002
DOI: 10.1128/iai.70.10.5533-5539.2002
|View full text |Cite
|
Sign up to set email alerts
|

Cholera Toxin and Heat-Labile Enterotoxin Activate Human Monocyte-Derived Dendritic Cells and Dominantly Inhibit Cytokine Production through a Cyclic AMP-Dependent Pathway

Abstract: Cholera toxin (CT) and heat-labile enterotoxin (LT) are powerful mucosal adjuvants whose cellular targets and mechanism of action are unknown. There is emerging evidence that dendritic cells (DC) are one of the principal cell types that mediate the adjuvant effects of these toxins in vivo. Here we investigate the effects of CT and LT on the maturation of human monocyte-derived DC (MDDC) in vitro. We found that an enzymatically active A domain is necessary for both CT and LT to induce the maturation of MDDC and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
121
1
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(138 citation statements)
references
References 30 publications
14
121
1
2
Order By: Relevance
“…This suggests that increased intracellular cAMP concentrations are involved in modulation of innate immune cell activation by CyaA. This conclusion is consistent with the observations that increases in intracellular cAMP concentration by stimuli such as cholera toxin or forskolin (23,24), lead to suppression of proinflammatory cytokines and chemokines, such as IL-12 and CXCL10 and enhancement of IL-10 and CCL17.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This suggests that increased intracellular cAMP concentrations are involved in modulation of innate immune cell activation by CyaA. This conclusion is consistent with the observations that increases in intracellular cAMP concentration by stimuli such as cholera toxin or forskolin (23,24), lead to suppression of proinflammatory cytokines and chemokines, such as IL-12 and CXCL10 and enhancement of IL-10 and CCL17.…”
Section: Discussionsupporting
confidence: 79%
“…Likewise, acylation of the RTX domain of CyaA is considered to be necessary for its hemolytic and cytotoxic activity (2,6,12). Previous studies have suggested that acylation is required for efficient adjuvanticity of CyaA, while the increase in intracellular cAMP levels generated by the adenylate cyclase domain is responsible for its immunomodulatory effects (5,6,23). Our data demonstrate that acylation is not essential for CyaA to induce cAMP accumulation in macrophages or to modulate activation of macrophages and DC.…”
Section: Discussionmentioning
confidence: 46%
“…Ctx causes increased plasma levels of cAMP through the ADP-ribosyltransferase activity of the A-subunit after binding of the B-subunit to the cell surface via the ubiquitous GM1 ganglioside [2,9,10,46]. Consistent with our observations for Ctx, cAMP-elevating agents can directly increase IL-10 production, inhibit TNFα secretion and MHC-II and CD40 expression, and reduce stimulatory capacity in murine DC [25].…”
Section: Discussionsupporting
confidence: 79%
“…Ctx or Ctx-B-subunit (Sigma, Taufkirchen, Germany) were added to MoDC cultures for 24 to 48 h on day 3 at final concentrations of 1 µg/mL, following previous studies with human and murine DC [2,18,19,22]. To exclude the influence of LPS contamination of the toxin preparation, Ctx detoxified with Detoxi-Gel TM AffinityPak TM Columns (Perbio Science, Bonn, Germany) was used in some experiments.…”
Section: Stimulation Of Modc Culturesmentioning
confidence: 99%
“…AKAPs have also been identified in dendritic cells, the major antigen presenting cells of the immune system [154]. Dendritic cell maturation and activity is regulated, amongst others, by PKA and cAMP [155]. Human dendritic cells express AKAP79, AKAP1, AKAP95, AKAP--Lbc and Ezrin; their expression upon maturation from a monocyte to a mature dendritic cell is differentially regulated: The expression of AKAP95 and Ezrin does not change, but that of AKAP79, AKAP1 and AKAP--Lbc increases and this is accompanied by a 1.8--fold increase of RIIα protein expression.…”
Section: Akaps In the Immune Systemmentioning
confidence: 99%